Measuring quality of life in the speaker with dysarthria: reliability and validity of the european portuguese version of the QoL-DyS - Nogueira, D.; Reis, E.; Ferreira, P.; Schindler, A. (Folia Phoniatrica et Logopaedica, 2019)
Background: The impact of acquired dysarthria on the person’s life and social participation is well recognized and is the key to the process of rehabilitation. Evaluation of the effectiveness of an intervention that addresses this impact is a challenge for clinicians and researchers. Objectives: The purpose of this study was to evaluate the validity and reliability of the European Portuguese version of the Quality of Life in the Speaker with Dysarthria (QoL-DyS). Methods: This research was conducted in three phases: (i) cultural and linguistic adaptation; (ii) feasibility and reliability; and (iii) validity. The sample was composed of 105 subjects with dysarthria and 103 healthy subjects. The QAD (Quick Assessment for Dysarthria), PEAT10 (Portuguese Eating Assessment Tool), and EQ-5D (EuroQol five-dimension scale) were used for validity and reliability. Results and Conclusion: The QoL-DyS correlated positively with the QAD, PEAT-10, and EQ5D. Cronbach’s ? was 0.973, and it remained excellent when any item was deleted. The QoL-DyS score mean difference between the non-dysarthric cohort and the dysarthric cohort was also significant. Confirmatory factor analysis did not validate the original 40-item scale but a 33-item scale maintaining the four domains of the original version. A significantly higher perception of QoL was found in the non-dysarthric group. The results indicate that the European Portuguese version of the QoL-DyS is a reliable and valid tool to assess QoL in patients with dysarthria and may be used for screening in clinical practice and in research.